2011
DOI: 10.4049/jimmunol.1002110
|View full text |Cite
|
Sign up to set email alerts
|

H2 Control of Natural T Regulatory Cell Frequency in the Lymph Node Correlates with Susceptibility to Day 3 Thymectomy-Induced Autoimmune Disease

Abstract: Day 3 thymectomy (D3Tx) results in a loss of peripheral tolerance mediated by natural regulatory T cells (nTregs) and development of autoimmune ovarian dysgenesis (AOD) and autoimmune dacryoadenitis (ADA) in A/J and (C57BL/6J × A/J) F1 hybrids (B6A), but not in C57BL/6J (B6) mice. Previously, using quantitative trait locus (QTL) linkage analysis, we showed that D3Tx-AOD is controlled by five unlinked QTL (Aod1-Aod5) and H2. In this study, using D3Tx B6-ChrA/J/NaJ chromosome (Chr) substitution strains, we confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…We show here that H 4 R signaling has a significant impact on regulating the proportion and distribution of natural T R cells in secondary lymphoid organs but not on their thymic development. These results support the concept that specific factors in the microenvironment of peripheral lymphoid tissues may dictate the fate of the immune response by influencing T R cell biology (i.e., the frequency and distribution of T R ) (38, 39). Naïve H 4 RKO mice have lower frequency of peripheral T R cells than WT mice and, upon MOG 35-55 immunization, exhibit more severe EAE.…”
Section: Discussionsupporting
confidence: 82%
“…We show here that H 4 R signaling has a significant impact on regulating the proportion and distribution of natural T R cells in secondary lymphoid organs but not on their thymic development. These results support the concept that specific factors in the microenvironment of peripheral lymphoid tissues may dictate the fate of the immune response by influencing T R cell biology (i.e., the frequency and distribution of T R ) (38, 39). Naïve H 4 RKO mice have lower frequency of peripheral T R cells than WT mice and, upon MOG 35-55 immunization, exhibit more severe EAE.…”
Section: Discussionsupporting
confidence: 82%
“…The expression of Eae5 candidates in T H ‐cell pathways suggested that either CD4 T H cells or Tregs might be affected as a result of the inheritance of SJL alleles at Eae5 . The frequency of natural Tregs (nTregs) in the lymph node is under the control of a gene within or tightly linked to H2 (del Rio and colleagues 23). The Eae5 locus lies just distal to H2 (Fig 4).…”
Section: Resultsmentioning
confidence: 99%
“…IL‐2 signaling plays a key role in immunomodulation through control of regulatory T‐cell homeostasis and function. Indeed, small perturbations in IL‐2 levels or in Treg frequency have been associated with differential susceptibility to EAE 23, 32. In addition, the environmentally derived factor VitD is physiologically immunoregulatory due, in part, to positive effects on Tregs 33, 34.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data, the resistance state of the B6 mice is a reflection of their strong intrinsic Treg function. This mechanism has been documented in autoimmune diabetes (35), and subsequently in autoimmune ovarian disease (36), autoimmune dacryoadenitis (37), and EAE (38). In all cases, disease resistance was mapped to the IL-2 locus in chromosome 3 (35), associated with enhanced production of IL-2 by activated T cells (35,39).…”
Section: Discussionmentioning
confidence: 99%